Importance of Neutrophil/Lymphocyte Ratio in Squamous-Cell Carcinoma of the Larynx - Muhammet fatih topuz; Adem Binnetoglu; Tekin Baglam; Ali Cemal Yumusakhuylu; Fetullah Gerin; Ozgur Baykan; Murat Sarı (Journal of Otolaryngology Advances, 2017)
Aim: The relation between inflammation and cancer has been known since the 19th century. However, investigations on the pathogenesis and pathophysiology of this relation have begun recently. It was demonstrated that increased neutrophil/lymphocyte ratio is a poor prognostic factor in some malignancies. The present study aimed to determine whether preoperative neutrophil/lymphocyte ratio has a prognostic value in larynx cancer. Method: Preoperative blood analyses of 139 patients, who underwent subtotal or total laryngectomy for larynx cancer between 2003 and 2013 at Marmara University School of Medicine, Department of ENT, were retrospectively evaluated. Neutrophil/lymphocyte ratio (NLR) was calculated dividing absolute neutrophil count by absolute lymphocyte count. Optimal cut-off value for NLR was determined by receiver operating characteristics (ROC) curve analysis. Statistical analyses were done using IBM SPSS statistic 22.0 (IBM SPSS, Turkey) and Med Calc 12.3.0 package programs. Results: The sensitivity of NLR in predicting advanced-stage (Stage 3 and 4) squamous-cell carcinoma of the larynx (LSSC), T4 LSSC and lymph node metastasis at different cut-off values were 66.2%, 83.9% and 73.8%, respectively and the specificity was 76.7%, 66.2% and 65.2%, respectively. Staging according to T classification revealed that NLR significantly increases with tumor stage (p<0.001). Statistically significant relation was determined between lymph node metastasis of tumor and neutrophil/lymphocyte ratio (p=0.003). Comparing overall survival (OS) and disease-free survival (DFS) between the cases with NLR <3.02 and the cases with NLR >3.02, it was demonstrated that OS and DFS are significantly lower in the cases with NLR<3.02 (p: 0.001 vs. p<0.05 for OS and p: 0.013 vs. p<0.05 for DFS) Conclusion: NLR increases with the stage of disease in LSSC. NLR is a simple, cheap, repeatable and valuable parameter that can be obtained from routine analyses, gives information about poor prognosis and survival, and is able to predict T4 LSSC, advanced-stage LSSC (stage 3-4) and lymph node metastasis.
Keywords: Neutrophil/lymphocyte ratio